Evaluation Methods in Biomedical and Health Informatics - Friedman, Charles P.; Wyatt, Jeremy C.; Ash, Joan S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This 3rd edition of Evaluation Methods in Biomedical and Health Informatics has been extensively revised and expanded. It builds on a solid foundation of evaluation theory to explain methods and techniques within health informatics, using many examples, real-world case studies and numerous self-tests with answers. Expanded to 20 rather than 12 chapters, new chapters have been added on qualitative methods, ethics, mixed methods, evidence-based informatics and how to conduct evaluation studies using routine, real-world data. Designed as a practical guide for masters and PhD students, informatics researchers and seasoned professionals seeking a comprehensive resource, this book describes health and biomedical information resource evaluation in a practical stepwise manner. Critiques and discussion of actual evaluation studies help to build the reader$1 (Bs knowledge of the judicious application of the techniques described. As information and communications technologies take on increasingly central roles in self-care, healthcare, biomedical research and education, understanding how to design and carry out successful rigorous evaluation studies becomes more imperative. Evaluation Methods in Biomedical and Health Informatics is an unparalleled reference for a broad range of health information professionals and is usable as both a textbook to support formal courses and a reference book for researchers and practitioners. From those training for careers in informatics to on-site biomedical information systems staff, this is an invaluable guide to the successful evaluation of digital healthcare, eHealth, telemedicine, electronic health records and other clinical and non-clinical information systems. .s
Challenges of Evaluation in Biomedical Informatics -- Evaluation as a Field -- Determining What to Study -- The Structure of Objectivist Studies -- Measurement Fundamentals -- Developing and Improving Measurement Methods -- The Design of Demonstration Studies -- Analyzing the Results of Demonstration Studies -- Subjectivist Approaches to Evaluation -- Performing Subjectivist Studies in the Qualitative Traditions Responsive to Users -- Economic Aspects of Evaluation -- Proposing and Communicating the Results of Evaluation Studies: Ethical, Legal, and Regulatory Issues.
Keywords: Medical informatics; Bioinformatics; Health Informatics; Health Informatics; Bioinformatics; Computational and Systems Biology; Medical Informatics; Evaluation Studies as Topic; Technology Assessment, Biomedical; Research Design